Tofacitinib in the treatment of Indian patients with rheumatoid arthritis: A post hoc analysis of efficacy and safety in Phase 3 and long‐term extension studies over 7 years. (1st June 2020) - Chopra, Arvind; Shobha, Vineeta; Chandrashekara, Srikantiah; Veeravalli, Sarath C. M.; Sharma, Reena; Rao, Uppuluri R.; Pandya, Sapan; Wagh, Shrikant; Kadel, Jugal K.; Thorat, Amit V.; Adhav, Charles; Santos Estrella, Paul; et al.
Abstract: Objectives: Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). We characterized tofacitinib efficacy/safety in Indian vs rest of the world (ROW; excluding India) RA patients. Methods: Efficacy data were pooled for disease‐modified antirheumatic drug (DMARD) inadequate responders from Phase (P)3 studies. For Indian patients, ORAL Solo and ORAL Scan; ROW (excluding India), these studies plus ORAL Step, ORAL Sync, and ORAL Standard. Safety data also included ORAL Start (P3; methotrexate‐naïve) and ORAL Sequel (long‐term extension [LTE] study; data cut‐off March 2017) for Indian patients, and these studies plus A3921041 (LTE study; Japanese study) for ROW. Efficacy outcomes at months 3/6: American College of Rheumatology (ACR)20/50/70; Disease Activity Score in 28 joints, erythrocyte sedimentation rate remission/low disease activity; change from baseline in Health Assessment Questionnaire‐Disability Index. Incidence rates (IRs; patients with events/100 patient‐years) for adverse events of special interest (AESIs) were assessed throughout. Descriptive data underwent no formal comparison. Results: One‐hundred‐and‐ninety‐seven Indian and 3879 ROW patients were included. Compared with ROW patients, Indian patients were younger, had lower body mass index, shorter RA duration, and higher baseline disease activity; most Indian patients were non‐smokers and all were biologic DMARD (bDMARD)‐naïve. Month 3 ACR20 rates with tofacitinib 5 mg twice daily/10 mg twice daily/placebo were 67.4%/82.1%/40.9% (India) and 59.0%/66.1%/28.2% (ROW), and month 6 rates were 76.2%/92.1%/88.9% (India) and 69.0%/74.2%/66.5% (ROW). Month 3/6 improvements in other outcomes were generally numerically greater with tofacitinib vs placebo, and similar in both populations. Compared with ROW, Indian patients had numerically fewer AEs/serious AEs, and similar IRs for discontinuations due to AEs and AESIs, except that tuberculosis (TB) IR was higher in Indian (IR = 1.21; 95% CI 0.49, 2.49) vs ROW patients (IR = 0.17; 95% CI 0.11, 0.25). Conclusions: Tofacitinib efficacy/safety were similar in both populations, except TB IR, which was higher in Indian patients but in line with those in bDMARD‐treated RA patients from high‐risk countries (IR = 0.00‐2.56; TB IR >0.05 [World Health Organization]). Limitations included the small Indian population and baseline differences between populations.